2018
DOI: 10.1186/s40001-018-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

No association of TP53 codon 72 and intron 3 16-bp duplication polymorphisms with breast cancer risk in Chinese Han women: new evidence from a population-based case–control investigation

Abstract: BackgroundMany studies have demonstrated that the genetic variants of tumor suppressor gene TP53 contribute to the prediction of breast cancer risk. However, most of them focused on Europeans and Americans; the investigations about Asians, especially Chinese women, are scarce. Thus, the aim of this study was to explore the influence of TP53 codon 72 and intron 3 16-bp duplication polymorphisms on the breast cancer risk in Chinese women, especially those from eastern China.MethodsBlood samples collected from 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…In this metaanalysis, we found that the Pro allele of p53 gene was associated with risk of breast cancer risk for Europeans and Africans when compared to Arg allele. This finding is consistent in part with a previous meta-analysis which investigated breast cancer risk in 41 cases unmatched control studies [50], but discordant with the finding reported by Hou et al 2013 [51], Zhuo et al [52] and Hao et al [53]. The difference between these results can be explained by the presence of heterogeneity between studies, and the mixture studies with age-matched and/or unmatched controls in their analysis.…”
Section: Discussionsupporting
confidence: 89%
“…In this metaanalysis, we found that the Pro allele of p53 gene was associated with risk of breast cancer risk for Europeans and Africans when compared to Arg allele. This finding is consistent in part with a previous meta-analysis which investigated breast cancer risk in 41 cases unmatched control studies [50], but discordant with the finding reported by Hou et al 2013 [51], Zhuo et al [52] and Hao et al [53]. The difference between these results can be explained by the presence of heterogeneity between studies, and the mixture studies with age-matched and/or unmatched controls in their analysis.…”
Section: Discussionsupporting
confidence: 89%
“…This observation was similar to those previously reported by in Morocco [19], in Iran [40], and Poland [42] but contradictory with the result obtained in Portugal [17]. In addition, we noted that the A2 allele was associated with the risk of breast cancer, which was consistent with the results of many authors [30,40] but different from the results reported by others [31,36]. The differences between studies may be explained by several factors such as sample size, race, ethnic differences, genetic background, environmental factors and heterogeity between the studies.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the influence of A2 allele on the alternative splicing of p53 protein causes an instability of the transcripts or proteins with modified functions. Many investigators have reported the existence of linkage disequilibrium between 6-bp duplication and other variants of TP53 such as codon 72 or p.Arg72Pro, intron 6 [31,45]. The codon 72 Arg/Pro, intron 3 16-bp duplication and intron 6 G > A TP53 haplotype was associated with the ability to repair DNA in lymphoblastic cell lines and apoptic reduction [21,46].…”
Section: Discussionmentioning
confidence: 99%
“…This observation was similar to those previously reported by in Morocco [20], in Iran [41], and Poland [43] but contradictory with the result obtained in Portugal [18]. In addition, we noted that the A2 allele was associated with the risk of breast cancer, which was consistent with the results of many authors [33,41] but different from the results reported by others [34,39]. The differences between studies may be explained by several factors such as sample size, race, ethnic differences, genetic background, environmental factors and heterogeity between the studies.…”
Section: Discussionsupporting
confidence: 78%